Pengembangan Video Tutorial Korean Make Up Look Teknik Ombre Lips pada Mata Kuliah Tata Rias Pengantin Internasional - Aurellia Yogi Ainanda Sekar; Sitti Nursetiawati; Aniesa Puspa Arum (Mathematics Education Study Program, 2025)
This research was compiled from the increasing interest of Indonesian people, especially students of the Cosmetology Education Study Program, towards Korean Beauty which focuses on Korean Make Up Look where students find some difficulties in applying Korean Make Up Look, especially in the ombre lips technique. This research uses a Research and Development model with a 4-D development model (define, design, develop, disseminate). This research developed a video tutorial on the Korean Make Up Look Ombre Lips Technique which aims to be a learning medium for the International Bridal Makeup course. The data collection technique used a questionnaire distribution with qualitative and quantitative data analysis techniques. The results of the research showed that the results of the material experts at one stage reached 94%. Furthermore, the validation test carried out by the media expert went through one stage and obtained a score of 86.6%. A one-to-one practicality test was also carried out with a score of 94% then continued with a small group test with a score of 97.9%. Based on this assessment, the video tutorial of Korean Make Up Look Ombre Lips Technique used as a learning medium in the International Bridal Make Up course was declared “Very Feasible” and “Very Practical”.